Factors Affecting the Utilization of Postnatal Care Services in Eastern Nepal - Khanal, Mukti Nath; KC , Vikash Kumar (Journal of Nobel Medical College, 2024)
Background: The importance of providing care to mothers after childbirth is critical for lowering maternal illness and death rates. This research aimed to analyze the factors influencing the use of postnatal services among mothers with having at least one living child three years preceding the survey in the Sunsari district of Eastern Nepal. Materials and Methods: A cross-sectional study was conducted within a community setting, involving 401 ever-married women of reproductive age group. The studyperformed bivariate and multivariate logistic regression analyses to identify factors associated with the utilization of postnatal care services. Results: Among 401 women studied, 52% had Postnatal Care (PNC) visits. Among those who utilized PNC services, the majority (96%) had partial utilization, while only 4.3% had complete PNC.PNC visits are more frequent among the wealthy, migrants, and upper castes, as well as those exposed to media, aware of health services, and perceiving higher service quality and awareness at health facilities. Conclusion: Both the coverage and complete utilization of PNC attendance were low. Increasing focus on mothers from poorer households, pockets of the native population, individuals needing behavioural modification, and those with poor awareness about available services may enhance the overall usage of complete PNC.